Layered tri-metallic catalytic articles and methods of making the same
By adopting a trimetal layered structure in the ternary conversion catalyst, replacing palladium with platinum and loading platinum and rhodium on different levels, the problems of high cost and supply shortage of palladium are solved, and the performance and emission treatment efficiency of the catalyst are improved.
Patent Information
- Application Number
- CN202080021890.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-16
- Filing Date
- 2020-03-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-03-18
AI Technical Summary
The high cost and supply shortage of palladium in existing ternary conversion catalysts makes it difficult to maintain or improve the performance of the catalyst by simply replacing palladium with platinum, especially when dealing with pollutants such as hydrocarbons, nitrogen oxides and When carbon monoxide.
Using a trimetal layered catalytic product, in which about 50% of the palladium is replaced by platinum, by loading palladium on the oxygen storage component and alumina component, platinum and rhodium on different levels, respectively, to form the weight of palladium and platinum. The ratio is in the range of 1.0:0.4 to 1.0:2.0 and calcined at a temperature of 400°C to 700°C to ensure the maintenance of catalyst performance.
It achieves a significant reduction in catalyst costs without reducing catalyst performance, improves the efficiency of treating hydrocarbons, carbon monoxide and nitrogen oxides in the exhaust gas, and meets the regulatory authorities' requirements for vehicle exhaust emissions.
Smart Images

Figure CN113574256B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the full priority benefit of U.S. Provisional Application No. 62 / 819695 filed on March 18, 2019 and European Application No. 19169497.5 filed on April 16, 2019. Technical Field
[0003] The presently claimed invention is directed to a layered catalytic article useful for treating exhaust gases to reduce pollutants contained therein. Specifically, the presently claimed invention is directed to a layered tri-metallic catalytic article and a method of making the same. Background Art
[0004] Three-way conversion (TWC) catalysts (hereinafter interchangeably referred to as three-way conversion catalysts, three-way catalysts, TWC catalysts and TWC) have been used for many years to treat the exhaust gas stream of internal combustion engines. Typically, in order to treat or purify the exhaust gas containing pollutants such as hydrocarbons, nitrogen oxides and carbon monoxide, a catalytic converter containing a three-way conversion catalyst is used in the exhaust gas line of the internal combustion engine. The three-way conversion catalyst is generally known for oxidizing unburned hydrocarbons and carbon monoxide and reducing nitrogen oxides.
[0005] Typically, most commercially available TWC catalysts contain palladium as the main platinum group metal component, which is used together with a smaller amount of rhodium. Since a large amount of palladium is used to make catalytic converters that help reduce the amount of exhaust gas pollutants, the market may see a shortage of palladium supply in the coming years. Currently, palladium is about 20-25% more expensive than platinum. At the same time, due to the reduction in the demand for platinum, the price of platinum is expected to fall. One of the reasons may be the decline in the production of diesel-powered vehicles.
[0006] Therefore, it is desirable to replace a portion of the palladium with platinum in a TWC catalyst in order to significantly reduce the cost of the catalyst. However, the proposed method is complicated by the need to maintain or improve the desired efficacy of the catalyst, which may not be achieved by simply replacing a portion of the palladium with platinum.
[0007] Therefore, the presently claimed invention focuses on providing a catalyst in which about 50% of the palladium is replaced by platinum without a decrease in overall catalyst performance, as described by comparing the following: individual CO, HC and NO x Comparison of conversion levels and non-methane hydrocarbons (NMHC) and nitrous oxide (NO) as a key requirement for vehicle certification by regulators in most jurisdictions x )’s total tail pipe emissions. Summary of the invention
[0008] The presently claimed invention provides a tri-metallic (Pt / Pd / Rh) layered catalytic article comprising: a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate wherein the weight ratio of palladium to platinum ranges from 1.0:0.4 to 1.0:2.0, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer. In one embodiment, the weight ratio of palladium to platinum ranges from 1.0:0.7 to 1.0:1.3. In one embodiment, the weight ratio of palladium to platinum to rhodium ranges from 1.0:0.7:0.1 to 1.0:1.3:0.3.
[0009] In one embodiment, the first layer is substantially free of platinum and rhodium. In one embodiment, the second layer may further include palladium supported on an alumina component.
[0010] On the other hand, the presently claimed invention provides a method for preparing a layered catalytic article, wherein the method comprises: preparing a first layer slurry; depositing the first layer slurry on a substrate to obtain a first layer; preparing a second layer slurry; and depositing the second layer slurry on the first layer to obtain a second layer, followed by calcination at a temperature in the range of 400°C to 700°C, wherein the step of preparing the first layer slurry or the second layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation and post-addition.
[0011] In still another aspect, the presently claimed invention provides an exhaust system for an internal combustion engine, the exhaust system comprising the layered catalytic article of the present invention.
[0012] The presently claimed invention provides a method of treating a gaseous exhaust stream comprising: hydrocarbons, carbon monoxide and nitrogen oxides, the method comprising contacting the exhaust stream with a layered catalytic article or exhaust system according to the present invention. The presently claimed invention further provides a method of reducing the levels of hydrocarbons, carbon monoxide and nitrogen oxides in a gaseous exhaust stream, the method comprising: contacting the gaseous exhaust stream with a layered catalytic article or exhaust system according to the present invention to reduce the levels of said hydrocarbons, carbon monoxide and nitrogen oxides in the exhaust gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] To provide an understanding of embodiments of the present invention, reference is made to the accompanying drawings, which are not necessarily drawn to scale and in which reference numerals refer to components of exemplary embodiments of the present invention. The drawings are exemplary only and should not be construed as limiting the present invention. The above and other features of the presently claimed invention, its nature and various advantages will become more apparent upon consideration of the following detailed description in conjunction with the accompanying drawings:
[0014] 1 is a schematic representation of a catalytic article design in an exemplary configuration according to some embodiments of the presently claimed invention.
[0015] FIG. 2 is a schematic representation of an exhaust system according to some embodiments of the presently claimed invention.
[0016] 3A , 3B and 3C are line graphs showing comparative test results of cumulative THC emissions, NO emissions and CO emissions of the inventive catalyst B and a reference catalyst.
[0017] Figure 4A A line graph showing comparative test results of cumulative HC emissions in the mid-bed and tailpipe of Inventive Catalyst A and a reference catalyst is presented.
[0018] Figure 4B A line graph showing comparative test results of cumulative CO emissions in the mid-bed and tailpipe of Inventive Catalyst A and a reference catalyst is presented.
[0019] Figure 4C A line graph showing comparative test results of cumulative NO emissions in the mid-bed and tailpipe of Inventive Catalyst A and a reference catalyst is presented.
[0020] 5A , 5B, and 5C are line graphs showing comparative test results of cumulative CO emissions, NO emissions, and THC emissions of Catalysts C, D, and E and a reference catalyst.
[0021] Fig. 6A is a perspective view of a honeycomb type substrate support that may include a catalyst composition according to one embodiment of the presently claimed invention.
[0022] Figure 6B is relative to Fig. 6A Zoom in and parallel to Fig. 6A A partial cross-sectional view taken through a plane of the end surface of a substrate carrier, showing Fig. 6A An enlarged view of the multiple air flow channels shown in FIG.
[0023] Figure 7 is relative to Fig. 6A A cross-sectional view of an enlarged portion of the Fig. 6A The honeycomb-type substrate in FIG. 1 represents the entire wall-flow filter substrate. DETAILED DESCRIPTION
[0024] The presently claimed invention will now be more fully described below. The presently claimed invention may be embodied in many different forms and should not be construed as limited to the embodiments described herein; rather, these embodiments are provided to make the presently claimed invention more thorough and complete, and to fully convey the scope of the invention to those skilled in the art. Language in this specification should not be construed to indicate that any non-claimed element is essential to the practice of the materials and methods of the present disclosure.
[0025] The terms "a," "an," "the," and similar referents used in the context of describing the materials and methods discussed herein (especially in the context of the following claims) are to be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context.
[0026] The term "about" as used in this specification is used to describe and illustrate small fluctuations. For example, the term "about" means less than or equal to ±5%, such as less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.2%, less than or equal to ±0.1% or less than or equal to ±0.05%. Whether or not explicitly stated, all numerical values herein are modified by the term "about". Values modified by the term "about" certainly include specific values. For example, "about 5.0" must include 5.0.
[0027] Unless otherwise indicated herein or otherwise clearly contradicted by context, all methods described herein can be performed in any suitable order. Unless otherwise stated, the use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better illustrate materials and methods and is not intended to limit the scope.
[0028] The present invention provides a tri-metallic layered catalytic article comprising three platinum group metals (PGMs) wherein a substantial amount of platinum may be used to substantially replace palladium.
[0029] Platinum group metals (PGM) refer to any component containing PGMs (Ru, Rh, Os, Ir, Pd, Pt and / or Au). For example, the PGM can be in a zero-valent metal form, or the PGM can be in an oxide form. Reference to a "PGM component" allows the PGM to exist in any valence state. The terms "platinum (Pt) component", "rhodium (Rh) component", "palladium (Pd) component", "iridium (Ir) component", "ruthenium (Ru) component", etc. refer to respective platinum group metal compounds, complexes, etc., which decompose or convert into a catalytically active form, typically a metal or metal oxide, when calcined or used as a catalyst.
[0030] In one embodiment, palladium and platinum are provided in separate layers to avoid the formation of alloys that may limit the effectiveness of the catalyst under certain conditions. Alloy formation may lead to core-shell structure formation and / or excessive PGM stabilization and / or sintering. When palladium is provided in the bottom layer and platinum and rhodium are provided in the top layer, it is found that the performance of the catalytic product is best, that is, the physical separation of platinum and palladium in different carrier coatings (washcoat) layers allows performance to be improved. In another embodiment, platinum and palladium are provided in the same layer, such as the top layer, wherein platinum or palladium or both are thermally fixed or chemically fixed on the support before slurry preparation. In the context of the present invention, the term "first layer" can be used interchangeably with "bottom layer" or "undercoat", and the term "second layer" can be used interchangeably with "top layer" or "top coating". The first layer is deposited on a substrate, and the second layer is deposited on the first layer.
[0031] The term "catalyst" or "catalytic article" or "catalyst article" refers to a composition in which a substrate is coated with a catalyst composition for promoting a desired reaction. In one embodiment, the catalytic article is a layered catalytic article. The term layered catalytic article refers to a catalytic article in which a substrate is coated with a PGM composition in a layered manner. These compositions may be referred to as washcoats.
[0032] The term “NO x ” refers to nitrogen oxide compounds, such as NO and / or NO2.
[0033] The platinum group metal is supported or impregnated on a support material such as an alumina component and an oxygen storage component. As used herein, "impregnated" or "impregnation" refers to the penetration of the catalytic material into the porous structure of the support material.
[0034] The "support" in a catalytic material or catalyst composition or catalyst washcoat refers to a material that receives metals (e.g., PGMs), stabilizers, promoters, binders, etc. by precipitation, association, dispersion, impregnation or other suitable methods. Exemplary supports include refractory metal oxide supports as described herein below.
[0035] "Refractory metal oxide supports" are metal oxides including, for example, massive alumina, ceria, zirconia, titania, silica, magnesia, neodymia, and other materials known for such uses, as well as physical mixtures or chemical combinations thereof, including atomically doped combinations, and including high surface area or active compounds such as activated alumina.
[0036] Exemplary combinations of metal oxides include alumina-zirconia, alumina-ceria-zirconia, lanthanum oxide-alumina, lanthanum oxide-zirconia-alumina, barium oxide-alumina, barium oxide-lanthanum oxide-alumina, barium oxide-lanthanum oxide-neodymium oxide-alumina, and alumina-ceria. Exemplary aluminas include macroporous boehmite, gamma-alumina, and delta / theta alumina. Useful commercial aluminas used as starting materials in the exemplary methods include activated aluminas such as high bulk density gamma-alumina, low or medium bulk density macroporous gamma-alumina, and low bulk density macroporous boehmite and gamma-alumina. Such materials are generally believed to provide durability to the produced catalyst.
[0037] A "high surface area refractory metal oxide support" specifically refers to a support having pores larger than and a wide pore distribution of support particles. High surface area refractory metal oxide supports (e.g., alumina support materials), also known as "gamma alumina" or "activated alumina," typically exhibit BET surface areas in excess of 60 square meters per gram ("m2 / g") for fresh material, and typically up to about 300 m2 / g or more. Such activated aluminas are typically a mixture of gamma and delta phases of alumina, but may also contain significant amounts of eta, kappa, and theta alumina phases.
[0038] Therefore, the present invention provides a tri-metallic layered catalytic product comprising: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an aluminum oxide component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.4 to 1.0:2.0, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0039] In one embodiment, the weight ratio of palladium to platinum ranges from 1:0.7 to 1:1.3. In one illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.7 to 1.0:1.3, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0040] In one embodiment, the weight ratio of palladium to platinum to rhodium is from 1.0:0.7:0.1 to 1.0:1.3:0.3. In one illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum to rhodium ranges from 1.0:0.7:0.1 to 1.0:1.3:0.3, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0041] In one embodiment, the tri-metallic layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an aluminum oxide component; a second layer, the second layer comprising platinum and rhodium, each supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.4 to 1.0:2.0, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer, wherein the first layer comprises 80 to 100 wt.% palladium based on the total weight of palladium present in the catalytic article.
[0042] In one embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.4 to 1.0:2.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer, wherein the first layer is substantially free of platinum and rhodium. As used herein, the term "substantially free of platinum and rhodium" means that there is no external addition of platinum and rhodium in the first layer, although it may optionally be present in a small amount of <0.001%.
[0043] In one embodiment, the first layer includes at least one alkaline earth metal oxide, the at least one alkaline earth metal oxide including barium oxide, strontium oxide, or any combination thereof, and the amount of the at least one alkaline earth metal oxide is 1.0 to 20 wt. % based on the total weight of the first layer.
[0044] In one embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.4 to 1.0:2.0, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer, wherein the second layer further comprises palladium supported on alumina, wherein the amount of palladium is 0.1 to 20 wt.% based on the total weight of palladium present in the catalytic article.
[0045] In an illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component and palladium supported on alumina; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.4 to 1.0:2.0. In an illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component and palladium supported on alumina component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.7 to 1.0:1.3, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0046] In an illustrative embodiment, the tri-metallic layered catalytic article comprises: a first layer comprising i) palladium supported on at least one of an oxygen storage component and an alumina component and ii) barium oxide; a second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component and palladium supported on an alumina component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.7 to 1.0:1.3, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0047] In one embodiment, the zirconium oxide component comprises at least 70% zirconium oxide.
[0048] In one embodiment, the platinum and / or palladium are thermally fixed or chemically fixed.
[0049] In one embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component and palladium supported on an alumina component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0:0.7 to 1.0:1.3, and the platinum and / or palladium present in the second layer is thermally fixed or chemically fixed, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0050] In one embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer being loaded with 1.0 to 300 g / ft 3 of palladium supported on the alumina component and the oxygen storage component; and a second layer, the second layer is loaded with 1.0 to 100 g / ft of palladium each supported on the oxygen storage component and / or the zirconium oxide component 3 Rhodium and 1.0 to 300 g / ft 3 of platinum, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0051] In one embodiment, 4.0 to 12 g / ft 3 In one exemplary embodiment, rhodium is used in an amount of 4 g / ft 3 In one embodiment, the amount of rhodium is 20 to 80 g / ft 3 In one exemplary embodiment, palladium is used in an amount of 38 g / ft 3 In one embodiment, palladium is used in an amount of 20 to 80 g / ft 3 In one exemplary embodiment, platinum is used in an amount of 38 g / ft 3 The amount of platinum used is .
[0052] In an illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer comprising palladium supported on the oxygen storage component and the alumina component; and a second layer comprising rhodium and platinum supported on the oxygen storage component and palladium supported on the alumina component, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0053] In one of the preferred embodiments, the weight ratio of palladium to platinum is 1.0:1.0. In an illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; a second layer, the second layer comprising platinum and rhodium supported on at least one of an oxygen storage component and a zirconium oxide component; and a substrate, wherein the weight ratio of palladium to platinum ranges from 1.0 to 1.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0054] In another illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium and platinum each supported on the oxygen storage component and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer. In another illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium and platinum each supported on the oxygen storage component and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer, wherein the platinum and / or palladium present in the second layer is thermally fixed or chemically fixed.
[0055] In another illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer comprising palladium and barium oxide supported on the oxygen storage component and the alumina component; and a second layer comprising rhodium and platinum, each supported on the oxygen storage component, and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0056] In another illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium and barium oxide supported on the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium and platinum, each supported on the oxygen storage component, and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, and the platinum and / or palladium present in the second layer is thermally fixed or chemically fixed, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0057] In still another illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium supported on the oxygen storage component and platinum supported on the oxygen storage component, wherein the weight ratio of palladium to platinum is 1.0:0.7 to 1.0:1.3, and wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer. In still another illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium supported on the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium supported on the oxygen storage component and platinum supported on the zirconium oxide component, wherein the weight ratio of palladium to platinum is 1.0:1.0, and wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer. In yet another illustrative embodiment, the first layer includes palladium supported on the oxygen storage component and the alumina component; and the second layer includes rhodium supported on the oxygen storage component and platinum supported on the zirconium oxide component, wherein the weight ratio of palladium to platinum is 1.0:1.0. In a further illustrative embodiment, the tri-metal layered catalytic article includes: a first layer, the first layer including palladium supported on the oxygen storage component and the alumina component and barium oxide; and a second layer, the second layer including rhodium supported on the oxygen storage component and platinum supported on the zirconium oxide component, wherein the weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0058] In another exemplary embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium and barium oxide supported on the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium and platinum supported on the oxygen storage component and palladium supported on the alumina component, wherein the weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer. In another exemplary embodiment, the tri-metal layered catalytic article comprises: a first layer, the first layer comprising palladium and barium oxide supported on both the oxygen storage component and the alumina component; and a second layer, the second layer comprising rhodium supported on the oxygen storage component and platinum supported on the lanthanum oxide-zirconia component, wherein the weight ratio of palladium to platinum is 1.0:1.0, wherein the first layer is deposited on the substrate, and the second layer is deposited on the first layer.
[0059] In one illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer comprising 30.4 g / ft 3of palladium and barium oxide supported on both the oxygen storage component and the alumina component; and a second layer comprising 4.0 g / ft 3 of rhodium and 38g / ft 3 of platinum and 7.6 g / ft2 supported on the alumina component 3 of palladium, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0060] In one illustrative embodiment, the tri-metal layered catalytic article comprises: a first layer comprising 38 g / ft 3 of palladium and barium oxide supported on both the oxygen storage component and the alumina component; and a second layer comprising 4 g / ft 3 of rhodium and 38 g / ft2 loaded on the lanthanum oxide-zirconia component 3 of platinum, wherein the first layer is deposited on the substrate and the second layer is deposited on the first layer.
[0061] As used herein, the term "oxygen storage component" (OSC) refers to an entity that has multiple valence states and can react actively with a reducing agent such as carbon monoxide (CO) and / or hydrogen under reducing conditions and then react with an oxidizing agent such as oxygen or nitrogen oxides under oxidizing conditions. Examples of oxygen storage components include ceria composites optionally doped with early transition metal oxides, specifically zirconium oxide, lanthanum oxide, praseodymium oxide, neodymium oxide, niobium oxide, europium oxide, samarium oxide, ytterbium oxide, yttrium oxide, and mixtures thereof.
[0062] In one embodiment, the oxygen storage component used in the first layer and / or the second layer comprises ceria-zirconia, ceria-zirconia-lanthanum oxide, ceria-zirconia-yttria, ceria-zirconia-lanthanum oxide-yttria, ceria-zirconia-neodymia, ceria-zirconia-praseodymia, ceria-zirconia-lanthanum oxide-neodymia, ceria-zirconia-lanthanum oxide-praseodymia, ceria-zirconia-lanthanum oxide-neodymia-praseodymia or any combination thereof, wherein the amount of the oxygen storage component is 20 to 80 wt.% based on the total weight of the first layer or the second layer. In an illustrative embodiment, the oxygen storage component comprises ceria-zirconia.
[0063] In one embodiment, the alumina component includes alumina, lanthanum oxide-alumina, ceria-alumina, ceria-zirconia-alumina, zirconia-alumina, lanthanum oxide-zirconia-alumina, barium oxide-alumina, barium oxide-lanthanum oxide-alumina, barium oxide-lanthanum oxide-neodymium oxide-alumina or a combination thereof; wherein the amount of the alumina component is 10 to 90 wt.% based on the total weight of the first layer or the second layer.
[0064] In one embodiment, the oxygen storage component comprises cerium dioxide, and the amount of cerium dioxide is 5.0 to 50 wt.% based on the total weight of the oxygen storage component. In one embodiment, the oxygen storage component of the first layer comprises cerium dioxide, and the amount of cerium dioxide is 20 to 50 wt.% based on the total weight of the oxygen storage component. In one embodiment, the oxygen storage component of the second layer comprises cerium dioxide, and the amount of cerium dioxide is 5.0 to 15 wt.% based on the total weight of the oxygen storage component.
[0065] In the context of the present invention, the term zirconium oxide component is a zirconium oxide based support stabilized or promoted by lanthanum oxide or barium oxide or ceria. Examples include lanthanum oxide-zirconia and barium oxide-zirconia.
[0066] As used herein, the term "substrate" refers to a monolithic material having a catalyst composition disposed thereon, typically in the form of a washcoat containing a plurality of particles containing the catalyst composition thereon.
[0067] References to a "monolithic substrate" or "honeycomb substrate" refer to a monolithic structure that is uniform and continuous from the inlet to the outlet.
[0068] As used herein, the term "washcoat" generally means in the art a thin adherent coating of a catalytic material or other material applied to a substrate material (such as a honeycomb-type substrate member) that is porous enough to allow the treated gas stream to pass through. Washcoat is formed by preparing a slurry of particles containing a certain solid content (e.g., 15-60% by weight) in a liquid vehicle, then applying the slurry to a substrate and drying to provide a washcoat layer.
[0069] As used herein and as described in Heck, Ronald and Farrauto, Robert, Catalytic Air Pollution Control (New York: Wiley-Interscience, 2002), pp. 18-19, a washcoat layer comprises a compositionally distinct layer of material disposed on a monolithic substrate surface or underlying washcoat layer. In one embodiment, the substrate contains one or more washcoat layers, and each washcoat layer differs in some manner (e.g., may differ in its physical properties, such as particle size or microcrystalline phase) and / or may differ in chemical catalytic function.
[0070] The catalytic article may be "fresh", which means that it is new and has not been exposed to any heat or thermal stress for a long period of time. "Fresh" may also mean that the catalyst was recently prepared and has not been exposed to any exhaust gas or high temperature. Likewise, an "aged" catalyst article is not fresh and has been exposed to exhaust gas and high temperature (i.e., greater than 500° C.) for a long period of time (i.e., greater than 3 hours).
[0071] According to one or more embodiments, the substrate of the catalytic article of the presently claimed invention can be composed of any material commonly used to prepare automotive catalysts, and generally includes a ceramic or metal monolithic honeycomb structure. In one embodiment, the substrate is a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymer foam substrate, or a woven fiber substrate.
[0072] The substrate generally provides a plurality of wall surfaces on which a washcoat including the catalyst composition described herein above is applied and adhered, thereby serving as a support for the catalyst composition.
[0073] Exemplary metal substrates include heat-resistant metals and metal alloys, such as titanium and stainless steel, and other alloys in which iron is a substantial or major component. Such alloys may contain one or more nickel, chromium and / or aluminum, and the total amount of these metals may advantageously include at least 15 wt.% of the alloy, such as 10 wt.%-25 wt.% chromium, 3%-8% aluminum, and up to 20 wt.% nickel. The alloy may also contain a small or trace amount of one or more metals, such as manganese, copper, vanadium, titanium, etc. The surface of the metal substrate may be oxidized at high temperatures (e.g., 1000° C. or higher) to form an oxide layer on the surface of the substrate, thereby improving the corrosion resistance of the alloy and promoting adhesion of the washcoat layer to the metal surface.
[0074] The ceramic material used to construct the substrate may include any suitable refractory material, for example, cordierite, mullite, cordierite-alumina, silicon nitride, zircon-mullite, spodumene, alumina-silica magnesia, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, alumina, aluminosilicates, and the like.
[0075] Any suitable substrate can be used, such as a monolithic flow-through substrate having a plurality of fine parallel gas flow channels extending from the inlet of the substrate to the outlet face so that the channel is open to allow fluid to flow. The channel, which is essentially a straight path from the inlet to the outlet, is defined by a wall, and the wall is coated with a catalytic material as a carrier coating so that the gas flowing through the channel contacts the catalytic material. The flow channel of the monolithic substrate is a thin-walled channel, and the thin-walled channel is in any suitable cross-sectional shape, such as a trapezoid, a rectangle, a square, a sinusoid, a hexagon, an ellipse, a circle, etc. Such a structure contains about 60 to about 1200 or more gas inlet openings (i.e., "cells") per square inch of cross section (cpsi), more typically about 300 to 900 cpsi. The wall thickness of the flow-through substrate can vary, with a typical range between 0.002 inches and 0.1 inches. A representative commercially available flow-through substrate is a cordierite substrate with a wall thickness of 400 cpsi and 6 mils or a wall thickness of 600 cpsi and 4 mils. However, it should be understood that the present invention is not limited to a specific substrate type, material or geometry. In an alternative embodiment, the substrate can be a wall-flow substrate, wherein each channel is blocked with a non-porous plug at one end of the substrate body, wherein the alternating channels are blocked at the opposite end faces. This requires the gas to flow through the porous walls of the wall-flow substrate to reach the outlet. Such a monolithic substrate can contain up to about 700 or more cpsi, for example, about 100 to 400 cpsi, and more typically about 200 to about 300 cpsi. The cross-sectional shape of the unit cell can be varied as described above. The wall thickness of the wall-flow substrate is generally between 0.002 inches and 0.1 inches. Representative commercially available substrates are composed of porous cordierite, examples of which are 200 cpsi and a wall thickness of 10 mils or 300 cpsi and a wall thickness of 8 mils, and a wall porosity of between 45% and 65%. Other ceramic materials such as aluminum titanate, silicon carbide and silicon nitride are also used as wall-flow filter substrates. However, it should be understood that the present invention is not limited to a particular substrate type, material or geometry. It is noted that where the substrate is a wall-flow substrate, the catalyst composition may penetrate into the pore structure of the porous wall (i.e., partially or completely occlude the pore openings) in addition to being disposed on the surface of the wall. In one embodiment, the substrate has a flow-through ceramic honeycomb structure, a wall-flow ceramic honeycomb structure, or a metal honeycomb structure.
[0076] As used herein, the term "stream" refers broadly to any combination of flowing gases that may contain solid or liquid particulate matter.
[0077] As used herein, the terms "upstream" and "downstream" refer to the relative directions of flow of the engine exhaust gas flow from the engine to the exhaust tailpipe, wherein the engine is located in the upstream position and the tailpipe and any pollutant abatement articles such as filters and catalysts are located downstream of the engine.
[0078] Fig. 6A and 6B An exemplary substrate 2 is shown in the form of a flow-through substrate coated with a washcoat composition as described herein. Fig. 6A , the exemplary substrate 2 has a cylindrical shape and a cylindrical outer surface 4, an upstream end face 6 and a corresponding downstream end face 8, the downstream end face being identical to the upstream end face 6. The substrate 2 has a plurality of parallel thin gas flow channels 10 formed therein. Figure 6B As shown, the flow channel 10 is formed by the wall 12 and extends through the substrate 2 from the upstream end face 6 to the downstream end face 8, and the channel 10 is unobstructed to allow a fluid (e.g., airflow) to flow longitudinally through the substrate 2 via its airflow channel 10. Figure 6B As can be more easily seen in the figure, the wall 12 is sized and configured so that the airflow channel 10 has a substantially regular polygonal shape. As shown, if desired, the washcoat composition can be applied in multiple, distinct layers. In the illustrated embodiment, the washcoat consists of a discrete first washcoat layer 14 adhered to the wall 12 of the substrate member and a second discrete second washcoat layer 16 coated on top of the first washcoat layer 14. In one embodiment, the presently claimed invention is also practiced with two or more (e.g., 3 or 4) washcoat layers and is not limited to the illustrated two-layer embodiment.
[0079] Figure 7 An exemplary substrate 2 is shown in the form of a wall flow filter substrate coated with a washcoat layer composition as described herein. Figure 7As shown, the exemplary substrate 2 has a plurality of channels 52. The channels are tubularly surrounded by the inner wall 53 of the filter substrate. The substrate has an inlet end 54 and an outlet end 56. Alternating channels are plugged with inlet plugs 58 at the inlet end and plugged with outlet plugs 60 at the outlet end to form a relative checkerboard pattern at the inlet 54 and the outlet 56. The gas flow 62 enters through the unblocked channel inlet 64, is blocked by the outlet plug 60, and diffuses to the outlet side 66 through the channel wall 53 (which is porous). The gas cannot return to the inlet side of the wall due to the inlet plug 58. The porous wall flow filter used in the present invention is catalyzed because the wall of the element has or contains one or more catalytic materials. The catalytic material can be present alone on the inlet side of the element wall, alone on the outlet side, on both the inlet side and the outlet side, or the wall itself can be composed of catalytic material in whole or in part. The present invention includes the use of one or more layers of catalytic material on the inlet and / or outlet wall of the element.
[0080] According to still another aspect, the presently claimed invention provides a method for preparing the catalytic article. In one embodiment, the method comprises: preparing a first layer slurry; depositing the first layer slurry on a substrate to obtain a first layer; preparing a second layer slurry; and depositing the second layer slurry on the first layer to obtain a second layer, followed by calcination at a temperature in the range of 400°C to 700°C, wherein the step of preparing the first layer slurry or the second layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation, and post-addition. In one embodiment, the method involves a preliminary step of thermally or chemically fixing platinum or palladium or both on a support.
[0081] Thermal fixation involves, for example, depositing the PGM onto the support by incipient wetness impregnation, followed by thermal calcination of the resulting PGM / support mixture. For example, the mixture is calcined at 400-700°C for 1-3 hours at a ramp rate of 1-25°C / min.
[0082] Chemical fixation involves depositing the PGM onto a support, followed by fixation with an additional reagent to chemically transform the PGM. For example, an aqueous solution of palladium nitrate is impregnated onto alumina. The impregnated powder is not dried or calcined, but added to an aqueous solution of barium hydroxide. As a result of the addition, acidic palladium nitrate reacts with alkaline barium hydroxide to produce water-insoluble palladium hydroxide and barium nitrate. Therefore, Pd is chemically fixed as an insoluble component in the pores and on the surface of the alumina support. Alternatively, the support can be impregnated with a first acidic component and then with a second alkaline component. The chemical reaction between the two reagents deposited on the support (e.g., alumina) results in the formation of insoluble or poorly soluble compounds, which are also deposited in the support pores and on the surface.
[0083] The incipient impregnation technique, also known as capillary impregnation or dry impregnation, is commonly used to synthesize heterogeneous materials, i.e., catalysts. Typically, active metal precursors are dissolved in an aqueous or organic solution, and then the metal-containing solution is added to a catalyst support containing a pore volume equal to the volume of the added solution. Capillary action draws the solution into the pores of the support. The added solution exceeds the volume of the support pores, causing the transport of the solution to be transformed from a capillary action process to a much slower diffusion process. The catalyst is dried and calcined to remove the volatile components in the solution, depositing the metal on the surface of the catalyst support. The concentration distribution of the impregnated material depends on the mass transfer conditions in the pores during impregnation and drying. Multiple active metal precursors can be co-impregnated onto the catalyst support after appropriate dilution. Alternatively, during the slurry preparation process, the active metal precursors are introduced into the slurry by post-addition under stirring.
[0084] The support particles are typically dried enough to absorb substantially all of the solution to form a wet solid. An aqueous solution of a water-soluble compound or complex of an active metal is typically used, such as rhodium chloride, rhodium nitrate, rhodium acetate, or a combination thereof, wherein rhodium is an active metal and palladium nitrate, palladium tetraamine, palladium acetate, or a combination thereof, wherein palladium is an active metal. After the support particles are treated with the active metal solution, the particles are dried, such as by heat treating the particles at an elevated temperature (e.g., 100-150° C.) for a period of time (e.g., 1-3 hours), and then calcined to convert the active metal into a more catalytically active form. An exemplary calcination process involves heat treatment in air at a temperature of about 400-550° C. for 10 minutes to 3 hours. The above process may be repeated as needed to achieve the desired loading level of the active metal by impregnation.
[0085] The catalyst composition as described above is usually prepared in the form of catalyst particles as described above. These catalyst particles are mixed with water to form a slurry to coat catalyst substrates such as honeycomb substrates. In addition to the catalyst particles, the slurry may optionally contain a binder, an associative thickener and / or a surfactant (including anionic, cationic, nonionic or amphoteric surfactants) in the form of aluminum oxide, silicon dioxide, zirconium acetate, zirconium oxide or zirconium hydroxide. Other exemplary binders include boehmite, γ-alumina or δ / θ alumina and silica sol. When present, the amount of binder is generally about 1wt.%-5wt.% of the total carrier coating loading. Acidic or alkaline substances are added to the slurry to adjust the pH accordingly. For example, in some embodiments, the pH of the slurry is adjusted by adding ammonium hydroxide, aqueous nitric acid or acetic acid. The typical pH range of the slurry is about 3 to 12.
[0086] The slurry may be ground to reduce particle size and enhance particle mixing. The grinding is done in a ball mill, a continuous mill or other similar equipment, and the solid content of the slurry may be, for example, about 20 wt.%-60 wt.%, more specifically about 20 wt.%-40 wt.%. In one embodiment, the slurry after grinding is characterized by D 90 The particle size is from about 3 to about 40 microns, preferably from 10 to about 30 microns, and more preferably from about 10 to about 15 microns. 90 Determined using a dedicated particle size analyzer. The equipment used in this example uses laser diffraction to measure particle size in a small volume of slurry. Typically, D 90 In micrometers it is meant that 90% of the particles by number have a diameter smaller than the stated value.
[0087] The slurry is coated on the catalyst substrate using any carrier coating technology known in the art. In one embodiment, the catalyst substrate is dipped in the slurry once or more or otherwise coated with the slurry. Thereafter, the coated substrate is dried at a high temperature (e.g., 100-150° C.) for a period of time (e.g., 10 minutes-3 hours), and then calcined by heating, for example, at 400-700° C., typically for about 10 minutes to about 3 hours. After drying and calcining, the final carrier coating coating is considered to be substantially free of solvent. After calcining, the catalyst loading obtained by the above-mentioned carrier coating technology can be determined by calculating the difference between the coated and uncoated weights of the substrate. As is apparent to those skilled in the art, the catalyst loading can be modified by changing the slurry rheology. In addition, the coating / drying / calcining process for producing the carrier coating can be repeated as needed to construct the coating to a desired loading level or thickness, which means that more than one carrier coating may be applied.
[0088] In certain embodiments, the coated substrate is aged by subjecting the coated substrate to a heat treatment. In one embodiment, aging is carried out at a temperature of about 850° C. to about 1050° C. in an environment of a 10 vol.% aqueous alternative hydrocarbon / air feed for 50-75 hours. Thus, an aged catalyst product is provided in certain embodiments. In certain embodiments, specifically effective materials include metal oxide-based supports (including but not limited to substantially 100% ceria supports) that maintain a high percentage (e.g., about 95-100%) of their pore volume when aged (e.g., at about 850° C. to about 1050° C., 10 vol.% aqueous alternative hydrocarbon / air feed, 50-75 hours aging).
[0089] On the other hand, the invention currently claimed provides an exhaust system for an internal combustion engine. The exhaust system includes a catalytic article as described herein above. In one embodiment, the exhaust system includes a platinum group metal-based three-way conversion (TWC) catalytic article and a layered catalytic article according to the present invention, wherein the platinum group metal-based three-way conversion (TWC) catalytic article is positioned downstream of the internal combustion engine, and the layered catalytic article is positioned downstream and is in fluid communication with the platinum group metal-based three-way conversion (TWC) catalytic article.
[0090] In another embodiment, the exhaust system includes a platinum group metal-based three-way conversion (TWC) catalytic article and a layered catalytic article according to the present invention, wherein the layered catalytic article is positioned downstream of the internal combustion engine, and the platinum group metal-based three-way conversion (TWC) catalytic article is positioned downstream and fluidly connected to the three-way conversion (TWC) catalytic article. Figure 2B and 2C The discharge system is shown in FIG.
[0091] In one illustrative embodiment, the exhaust system includes: a) a layered catalytic article comprising: i) a first layer comprising Pd supported on OSC, Pd supported on alumina, and barium oxide; and ii) a second layer comprising Rh and Pt supported on OSC, and Pd supported on alumina; and b) a TWC catalyst comprising i) a first layer comprising Pd and barium oxide supported on OSC and alumina; and ii) a second layer comprising Rh supported on alumina and OSC. Figure 2B , wherein a CC1 catalyst IC-1 (a catalytic article of the present invention) is positioned in fluid communication with an internal combustion engine, and a CC2 catalyst RC-2 (a reference CC catalyst) is positioned in fluid communication with the CC1 catalyst.
[0092] Figure 2A A reference exhaust system is presented, wherein the CC1 RC-1 catalyst comprises: i) a first layer comprising Pd and barium oxide supported on OSC and alumina; and ii) a second layer comprising Rh supported on alumina and Pd supported on OSC; and the CC2-RC-2 catalyst comprises: i) a first layer comprising Pd and barium oxide supported on OSC and alumina; and ii) a second layer comprising Rh supported on alumina and Pd supported on OSC.
[0093] In another illustrative embodiment, the exhaust system includes: a) a layered catalytic article comprising: i) a first layer comprising Pd supported on OSC, Pd supported on alumina, and barium oxide; and ii) a second layer comprising Rh supported on OSC and Pt supported on lanthanum oxide-zirconia; and b) a TWC catalyst comprising i) a first layer comprising Pd supported on OSC and alumina, and barium oxide; and ii) a second layer comprising Rh supported on alumina and OSC. Figure 2C , wherein a CC1 catalyst IC-2 (a catalytic article of the present invention) is positioned in fluid communication with an internal combustion engine, and a CC2 catalyst RC-2 (a reference CC catalyst) is positioned in fluid communication with the CC1 catalyst.
[0094] On the one hand, the invention currently claimed also provides a method for treating a gaseous exhaust stream including hydrocarbons, carbon monoxide and nitrogen oxides. The method involves contacting the exhaust stream with a catalytic product or exhaust system according to the invention currently claimed. The terms "exhaust stream", "engine exhaust stream", "exhaust gas stream" and the like refer to any combination of flowing engine exhaust gases, which may also contain solid or liquid particulate matter. The stream includes gaseous components, and is, for example, the exhaust of a lean-burn engine, which may contain certain non-gaseous components, such as droplets, solid particles, etc. The exhaust stream of a lean-burn engine typically includes combustion products, products of incomplete combustion, nitrogen oxides, combustible and / or carbonaceous particulate matter (soot) and unreacted oxygen and / or nitrogen. Such terms also refer to the effluent downstream of one or more other catalyst system components as described herein. In one embodiment, a method for treating an exhaust stream containing carbon monoxide is provided.
[0095] In another aspect, the presently claimed invention also provides a method of reducing the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in a gaseous exhaust stream. The method involves contacting the gaseous exhaust stream with a catalytic article or exhaust system according to the presently claimed invention to reduce the levels of the hydrocarbons, carbon monoxide, and nitrogen oxides in the exhaust gas.
[0096] In still another aspect, the presently claimed invention also provides a use of the catalytic article of the presently claimed invention for purifying a gaseous exhaust stream comprising hydrocarbons, carbon monoxide, and nitrogen oxides.
[0097] In some embodiments, the catalytic article converts at least about 60% or at least about 70% or at least about 75% or at least about 80% or at least about 90% or at least about 95% of the amount of carbon monoxide, hydrocarbons, and nitrous oxide present in the exhaust gas stream prior to contact with the catalytic article. In a certain embodiment, the catalytic article converts hydrocarbons into carbon dioxide and water. In some embodiments, the catalytic article converts at least about 60% or at least about 70% or at least about 75% or at least about 80% or at least about 90% or at least about 95% of the amount of hydrocarbons present in the exhaust gas stream prior to contact with the catalytic article. In a certain embodiment, the catalytic article converts carbon monoxide into carbon dioxide. In a certain embodiment, the catalytic article converts nitrogen oxides into nitrogen.
[0098] In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of nitrogen oxides present in the exhaust gas stream prior to contact with the catalytic article. In a certain embodiment, the catalytic article converts at least about 50%, or at least about 60%, or at least about 70%, or at least about 80%, or at least about 90%, or at least about 95% of the total amount of hydrocarbons, carbon monoxide, and nitrogen oxides present in the exhaust gas stream combined prior to contact with the catalytic article.
[0099] Examples
[0100] Various aspects of the presently claimed invention are more fully illustrated by the following examples, which are set forth for the purpose of illustrating certain aspects of the invention and should not be construed as limitations of the invention.
[0101] Example 1: Preparation of reference catalytic product (CC1 RC-1, bimetallic catalyst: Pd:Rh (1:0.052))
[0102] A Pd / Rh based TWC catalytic article was prepared as a close coupled catalyst. The total PGM loading (Pd / Pt / Rh) was 76 / 0 / 4. The basecoat contained 68.4 g / ft 3 The top coating contains 7.6 g / ft 3 Pd and 4g / ft 3 Rh or 10% of the total Pd and 100% of the total Rh in the catalyst. The washcoat loading of the basecoat was 2.34 g / inch 3 , and the top coat carrier coating loading was 1.355 g / inch 3The primer layer was prepared by impregnating 60% palladium nitrate solution (43.3 g, 28% palladium nitrate in water) on 314 g alumina and 40% palladium nitrate solution (28.9 g, 28% palladium nitrate in water) on 785 g ceria-zirconia. The alumina portion was chemically fixed by adding the Pd / alumina mixture to an aqueous solution of 85.6 g barium acetate in water. 39 g barium sulfate was also added to the mixture. This component was then ground to D 90 Less than 16 μm. If necessary, control the pH to around 4-5 by adding nitric acid. Add the ceria-zirconia portion to water and grind to D 90 Less than 16 μm. If necessary, the pH is controlled at around 4-5 by adding nitric acid. The two components are then blended and 128 grams of alumina binder is added to the blend.
[0103] The top coating has two components. The first component is prepared by impregnating a mixture of 20.7 g of rhodium nitrate (Rh content 9.9%) and 80.5 g of neodymium nitrate (Nd2O3 content 27.5%) in 560 g of water on 903 g of alumina. This step is followed by calcination at 500°C for 2 hours to allow the PGM to be fixed on the support. The resulting powder is then mixed with water and ground to D 90 The second component was prepared by impregnating 13.8 g of palladium nitrate (Pd content 28%) mixed with water on 260.4 g of ceria-zirconia, followed by calcination at 500°C for 2 hours to allow the PGM to be fixed on the support. The resulting powder was then mixed with water and ground to D 90 Less than 16 μm. If necessary, the pH is controlled at about 4-5 by adding nitric acid. The two slurries thus obtained are blended and 156 grams of alumina binder are added. If necessary, the pH is controlled at about 4-5 by adding nitric acid. The catalytic article is prepared by first applying the undercoat slurry to a 600 / 3.5 ceramic substrate. The coated substrate obtained is then dried and calcined at 500°C for 2 hours. Then, a second (topcoat) slurry is applied. The resulting product is calcined again at 500°C for 2 hours.
[0104] Example 2: Preparation of a catalytic article according to the invention (CC 1IC-A, trimetallic-top layer containing Pd, Pt and Rh and bottom layer containing Pd (ratio: 1.0:1.0:0.105), thermally fixed)
[0105] Catalytic products were formulated using Pt, Pd and Rh to produce a 38 / 38 / 4 design. Total PGM loading was 80 g / ft 3 , and the base coat contains 30.4 g / ft 3of Pd or 80% of the total Pd in the catalyst. The top coating contains 7.6 g / ft 3 Pd, 38g / ft 3 Pt and 4g / ft 3 Rh or 20% of the total Pd in the catalyst and 100% of the total Pt and Rh. The washcoat loading of the basecoat was 2.318 g / inch 3 , and the top coat washcoat loading was 1.352 g / in 3 The undercoat was prepared by impregnating 60% palladium nitrate solution (24.3 g, 28% palladium nitrate in water) on 396 g alumina and 40% palladium nitrate solution (16.2 g, 28% palladium nitrate in water) on 990.6 g ceria-zirconia. The alumina portion was chemically fixed by adding the Pd / alumina mixture to an aqueous solution of 108 g barium acetate in water. 49.3 g barium sulfate was also added to the mixture. This component was then ground to D 90 Less than 16 μm. If necessary, control the pH to around 4-5 by adding nitric acid. Add the ceria-zirconia portion to water and grind to D 90 Less than 16 μm. If necessary, the pH is controlled at around 4-5 by adding nitric acid. The two components are then blended and 161 grams of alumina binder are added.
[0106] The top coating has two components. The first component is prepared by impregnating a mixture of 17.3 g of palladium nitrate (Pd content 28%) in 200 g of water on 283 g of alumina. This step is followed by calcination at 500°C for 2 hours to allow the PGM to be fixed on the support. The resulting powder is then mixed with water and ground to D 90 Less than 16 μm. If necessary, the pH is controlled at about 4-5 by adding nitric acid. The second component is prepared by impregnating 170.9 g of platinum nitrate (Pt content 14.3%) and 25.9 g of rhodium nitrate (Rh content 9.9%) mixed with water on 1175.4 g of ceria-zirconia, followed by calcination at 500°C for 2 hours to allow the PGM to be fixed on the support. The resulting powder is then mixed with water and ground to D 90Less than 16 μm. If necessary, the pH is controlled at about 4-5 by adding nitric acid. The two slurries thus obtained are blended and 194 grams of alumina binder are added. If necessary, the pH is controlled at about 4-5 by adding nitric acid. The catalytic article is prepared by first applying the undercoat slurry to a 600 / 3.5 ceramic substrate. The coated substrate obtained is then dried and calcined at 500°C for 2 hours. Then, a second topcoat slurry is applied. The resulting product is calcined again at 500°C for 2 hours. Comparative tests show that the catalytic article of the present invention shows improved THC, NO and CO reduction compared to the reference catalytic article RC-1. The results are shown in the accompanying drawings.
[0107] Example 3: Preparation of a catalytic article of the invention (CC 1IC-B, trimetallic - separate layers containing Pt and Pd (top layer: Rh+Pt, bottom layer: Pd, ratio: 1.0:1.0:0.105)
[0108] Catalytic products were formulated using Pt, Pd and Rh to produce a 38 / 38 / 4 design. Total PGM loading was 80 g / ft 3 , and the base coat contains 38g / ft 3 of Pd or 100% of the total Pd in the catalyst. The top coating contains 38 g / ft 3 Pt and 4g / ft 3 The carrier coating loading of the base coat is 2.322 g / inch 3 , and the top coat washcoat loading was 1.347 g / in 3 The undercoat was prepared by impregnating 60% palladium nitrate solution (30.3 g, 28% palladium nitrate in water) on 395.5 g alumina and 40% palladium nitrate solution (20.2 g, 28% palladium nitrate in water) on 988.8 g ceria-zirconia. The alumina portion was chemically fixed by adding the Pd / alumina mixture to 108 g of an aqueous solution of barium acetate in water. 49.2 g of barium sulfate was also added to the mixture. This component was then ground to D 90 Less than 16 μm. If necessary, control the pH to around 4-5 by adding nitric acid. Add the ceria-zirconia portion to water and grind to D 90 Less than 16 μm. If necessary, the pH is controlled at around 4-5 by adding nitric acid. The two components are then blended and 161.5 grams of alumina binder are added.
[0109] The top coating has two components. The first component is prepared by impregnating a mixture of 26 grams of rhodium nitrate (Rh content 9.9%) in 320 grams of water on 731.6 grams of ceria-zirconia. This step is followed by calcination at 500°C for 2 hours to allow the PGM to be fixed on the support. The second component is prepared by impregnating 171.4 grams of platinum nitrate (Pt content 14.3%) mixed with water on 731.6 grams of lanthanum oxide-zirconia, followed by calcination at 500°C for 2 hours to allow the PGM to be fixed on the support. The two component powders are then mixed with water and ground to D 90 Less than 16 μm. The slurry thus obtained is mixed with 194.8 grams of alumina binder. If necessary, the pH is controlled at about 4-5 by adding nitric acid. The catalytic article is prepared by first applying the undercoat slurry to a 600 / 3.5 ceramic substrate. The coated substrate obtained is then dried and calcined at 500°C for 2 hours. Then, a second (topcoat) slurry is applied. The resulting product is calcined again at 500°C for 2 hours. In the accompanying drawings, Figure 1A and 1B The catalytic products A and B of the present invention are shown in Figure 1C The reference catalytic article is shown in . Comparative testing shows that the catalytic article of the present invention shows improved THC, NO and CO reduction compared to the reference catalytic article RC-1. The results are shown in the accompanying figures.
[0110] Example 4: Preparation of Catalytic Products (Catalytic Products C; Catalytic Products D and Catalytic Products E, with Supports with Varying Pd / Pt-Containing Underlayers, Out of Range)
[0111] Catalyst preparations C, D and E were prepared to examine their efficacy when Pd was directly substituted for Pt in the reference CC TWC design. The substitution was done by replacing 50% of the Pd with 50% of the Pt by weight. The catalyst designs are provided in the table below:
[0112] Table 1: Catalytic product design
[0113]
[0114] The undercoat layer of catalytic article C was prepared by using a Pd / Pt mixture split identically between alumina and ceria-zirconia, while the topcoat layer remained identical to that of the reference catalyst, i.e., it contained Pd on ceria-zirconia and Rh on alumina. The undercoat layer of catalytic article D was prepared using Pd on ceria-zirconia and Pt on alumina, while the topcoat layer was prepared using Rh on ceria-zirconia and Pt on alumina. The undercoat layer of catalytic article E was prepared using Pd on alumina and Pt on ceria-zirconia, while the topcoat layer was prepared using Rh on ceria-zirconia and Pt on alumina. The washcoat loadings remained identical to those in the reference.
[0115] The catalyst was prepared by first applying the undercoat slurry onto a 600 / 3.5 ceramic substrate. The coated substrate obtained was then dried and calcined at 500°C for 2 hours. Then, a second (topcoat) slurry was applied. The resulting product was calcined again at 500°C for 2 hours. Comparative testing showed that catalytic articles C, D and E showed lower THC, NO and CO reductions compared to the reference catalytic article RC-1. The results are shown in the accompanying drawings.
[0116] Example 5: Preparation of a Second Closely Coupled TWC Reference Catalyst Article (CC2 RC-2 Catalyst Article)
[0117] A reference CC2 TWC catalytic article (Pd / Pt / Rh: 14 / 0 / 4) was prepared and used in all the following examples in the second close coupling position. The catalyst was prepared by mixing 718.5 g of alumina with water, controlling the pH to about 4-5 by adding nitric acid, and then grinding to D 90 The primer layer was prepared with a thickness of less than 16 μm. Then 716.2 g of ceria-zirconia was added to the slurry. Then 27.7 g of Pd (Pd content 27.3%) was added to the slurry, and after brief mixing, the slurry was ground again to D 90 Less than 14 μm. In the next step, 71.5 grams of barium sulfate and 239.2 grams of alumina binder were added and the final slurry was mixed for 20 minutes.
[0118] The top coating consists of two components. The first component is prepared by impregnating 367 grams of water containing 11.3 grams of rhodium nitrate (Rh content 9.8%) on 483 grams of alumina. The powder is then added to the water and methyl-ethyl-amine (MEA) is added until the pH is equal to 8. The slurry is then mixed for 20 minutes and the pH is lowered to 5.5-6 using nitric acid. The slurry is then ground to D 90Less than 14 μm. The second component is prepared by impregnating 11.3 g of rhodium nitrate (Rh content 9.8%) mixed with 550 g of water on 979.3 g of ceria-zirconia. The powder is then added to water and methyl-ethyl-amine (MEA) is added until the pH is equal to 8. The slurry is then mixed for 20 minutes. 80.6 g of zirconium nitrate (ZrO2 content 19.7%) is added to it and, if necessary, the pH is lowered to 5.5-6 using nitric acid. The slurry is then ground to D 90 The two obtained slurries were then blended, 245 grams of alumina binder were added and, if necessary, the pH was controlled around 4-5 by adding nitric acid.
[0119] The catalytic article was prepared by first coating the undercoat slurry onto a 600 / 3.5 ceramic substrate. The resulting coated substrate was then dried and calcined at 500°C for 2 hours. Then, a second (topcoat) slurry was applied. The resulting product was calcined again at 500°C for 2 hours.
[0120] Example 6: Preparation and testing of catalyst system A of the present invention (CC1 IC-A+CC2 RC-2):
[0121] Catalyst system A comprising the inventive catalytic product A (Pd / Pt / Rh: 38 / 38 / 4) and the reference CC2 catalytic product (Pd / Pt / Rh: 14 / 0 / 4) was prepared and compared with a reference system comprising the reference CC1 catalytic product (Pd / Pt / Rh: 76 / 0 / 4) and the reference CC2 catalytic product (Pd / Pt / Rh: 14 / 0 / 4). Figure 2B Catalyst system A is shown in Figure 2A The reference system is shown in Figure 2. Both systems were engine aged at 950°C for 50 hours under alternating feed conditions and subsequently tested on a SULEV-30 certified light-duty vehicle using the FTP-75 test protocol. The claimed catalyst system A showed TWC performance improvements over the reference system, with a 17% improvement in THC, a 20% improvement in CO and a 20% improvement in NO in the mid-bed. x Improved by 17%, and THC in the tailpipe improved by 20%, CO improved by 24% and NO x An improvement of 18%. Thus, the 38 / 38 / 4 trimetallic catalyst not only meets the performance of the Pd / Rh 0 / 76 / 4 reference, but also provides an improvement over the reference. The results are shown in Figure 4A , 4B and 4C.
[0122] Example 7: Preparation and testing of catalyst system B of the present invention: (CC1 IC-B + CC2 RC-2):
[0123] A system comprising the inventive catalytic product B (Pd / Pt / Rh: 38 / 38 / 4) and the reference CC2 catalytic product (Pd / Pt / Rh: 14 / 0 / 4) was prepared and compared with a reference system comprising the reference CC1 catalytic product (Pd / Pt / Rh: 76 / 0 / 4) and the CC2 catalytic product (Pd / Pt / Rh: 14 / 0 / 4). Figure 2C Catalyst system B is shown in Figure 3. Both systems were reactor aged at 980°C for 12 hours under alternating feed conditions and then tested using a reactor simulating a SULEV-30 certified light vehicle. The reactor was set up so that the lambda, temperature and speed trajectory matched the lambda, temperature and speed trajectory of the vehicle under FTP-72 test conditions. The claimed system B showed TWC performance improvement, with mid-bed results of 21% improvement in THC, 33% improvement in CO and 28% improvement in NO. The results are shown in Figure 3.
[0124] The catalyst system designs are provided in the table below.
[0125] Table 2: Catalyst system design
[0126]
[0127] Findings / Results
[0128] From the results shown in the above examples and figures, it can be found that direct incorporation of platinum into existing Pd / Rh catalysts by replacing 50% of Pd with Pt is not the most effective approach for Pt utilization. As shown in Example 4 and Figures 5A, 5B and 5C, this approach typically results in up to 30% increase in hydrocarbon, CO and nitrous oxide emissions, depending on the type of emissions. In addition, this increase occurs regardless of whether Pt and Pd are mixed on the same support or present on different supports, as long as the corresponding metals are not thermally or chemically fixed before the catalyst is washed.
[0129] The above disadvantages are solved in the currently claimed inventive catalytic articles A and B (Examples 2 and 3), in which Pd and Pt are distributed on different support types and / or in different layers of the catalytic article. Pd and Pt can be present in the same layer (inventive catalytic article B) as long as the metals are chemically or thermally fixed before slurry coating. In the case of the reported examples, both designs demonstrated improvements compared to the reference system that typically range between 20% and 30%, depending on the type of emission. There are improvements both in the mid-bed and in the tail pipe, which demonstrates the activity of the Pt-containing system itself, rather than the compensating effect of the CC2 catalytic article. The results are shown in Figures 3, 4 and 6.
[0130] Throughout this specification, references to "one embodiment", "certain embodiments", "one or more embodiments" or "embodiments" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiments are included in at least one embodiment of the invention currently claimed. Therefore, words appearing in different places throughout the specification, such as "in one or more embodiments", "in certain embodiments", "in some embodiments", "in one embodiment" or "in an embodiment", do not necessarily refer to the same embodiment of the invention currently claimed. In addition, in one or more embodiments, specific features, structures, materials or characteristics can be combined in any suitable manner. All various embodiments, aspects and options disclosed herein can be combined in all variations, regardless of whether such features or elements are explicitly combined in the specific embodiment descriptions herein. The invention currently claimed is intended to be read as a whole, so that any separable features or elements of the disclosed invention should be considered to be intended to be combinable in any of its various aspects and embodiments, unless the context clearly indicates otherwise.
[0131] Although the embodiments disclosed herein have been described with reference to specific embodiments, it should be understood that these embodiments are merely illustrations of the principles and applications of the invention currently claimed. It will be apparent to those skilled in the art that various modifications and variations may be made to the methods and apparatus of the invention currently claimed without departing from the spirit and scope of the invention currently claimed. Therefore, the invention currently claimed is intended to be included in the modifications and variations within the scope of the appended claims and their equivalents, and the embodiments described above are presented for purposes of illustration and not limitation. All patents and publications cited herein are incorporated herein by reference for their specific teachings as mentioned, unless other incorporation statements are specifically provided.
Claims
1. A tri-metal layered catalytic product comprising: a) a first layer comprising palladium supported on at least one of an oxygen storage component and an alumina component; b) a second layer comprising platinum and rhodium each supported on at least one of an oxygen storage component and a zirconium oxide component; and c) substrate, The weight ratio of palladium to platinum is in the range of 1.0:0.7 to 1.0:1.3, wherein the platinum and / or palladium are fixed thermally or chemically on the support, wherein the thermal fixing involves depositing the platinum and / or palladium on the support and then thermally calcining the resulting mixture of platinum and / or palladium and the support; wherein the chemical fixing involves depositing the platinum and / or palladium on the support and then fixing with an additional reagent to chemically convert the platinum and / or palladium, The first layer is deposited on the substrate, and the second layer is deposited on the first layer.
2. The layered catalytic article according to claim 1, wherein the weight ratio of palladium to platinum ranges from 1.0:1.0 to 1.0:1.
3.
3. The layered catalytic article of claim 1, wherein the weight ratio of palladium to platinum is 1.0:1.
0.
4. The layered catalytic article of claim 1, wherein the weight ratio of palladium to platinum to rhodium ranges from 1.0:0.7:0.1 to 1.0:1.3:0.
3.
5. The layered catalytic article according to any one of claims 1 to 4, wherein the first layer comprises 80 to 100 wt.% palladium, based on the total amount of palladium present in the catalytic article.
6. The layered catalytic article according to any one of claims 1 to 4, wherein the oxygen storage components of the first layer and the second layer include ceria-zirconia, ceria-zirconia-lanthanum oxide, ceria-zirconia-yttria, ceria-zirconia-lanthanum oxide-yttria, ceria-zirconia-neodymia, ceria-zirconia-praseodymia, ceria-zirconia-lanthanum oxide-neodymia, ceria-zirconia-lanthanum oxide-praseodymia, ceria-zirconia-lanthanum oxide-neodymia-praseodymia or any combination thereof, wherein the amount of the oxygen storage components is 20 to 80 wt.% based on the total weight of the first layer.
7. The layered catalytic article according to any one of claims 1 to 4, wherein the alumina component comprises alumina, lanthanum oxide-alumina, ceria-alumina, ceria-zirconia-alumina, zirconia-alumina, lanthanum oxide-zirconia-alumina, barium oxide-alumina, barium oxide-lanthanum oxide-alumina, barium oxide-lanthanum oxide-neodymium oxide-alumina or a combination thereof; wherein the amount of the alumina component is 10 to 90 wt.% based on the total weight of the first layer.
8. The layered catalytic article according to any one of claims 1 to 4, wherein the zirconium oxide component comprises lanthanum oxide-zirconia and barium oxide-zirconia.
9. The layered catalytic article according to any one of claims 1 to 4, wherein the first layer is substantially free of platinum and rhodium.
10. The layered catalytic article according to any one of claims 1 to 4, wherein the first layer comprises at least one alkaline earth metal oxide, the at least one alkaline earth metal oxide comprising barium oxide, strontium oxide or any combination thereof, and the amount of the at least one alkaline earth metal oxide is 1.0 to 20 wt.% based on the total weight of the first layer.
11. The layered catalytic article according to any one of claims 1 to 4, wherein the zirconium oxide component comprises at least 70 wt.% zirconium oxide, based on the total weight of the zirconium oxide component.
12. The layered catalytic article according to any one of claims 1 to 4, wherein the oxygen storage component of the first layer comprises cerium dioxide in an amount of 20 to 50 wt.%, based on the total weight of the oxygen storage component, and the oxygen storage component of the second layer comprises cerium dioxide in an amount of 5 to 15 wt.%, based on the total weight of the oxygen storage component.
13. The layered catalytic article according to any one of claims 1 to 4, wherein the second layer further comprises palladium supported on an alumina component, wherein the amount of palladium is 0.1 to 20 wt. % based on the total weight of palladium present in the catalytic article.
14. The layered catalytic article according to any one of claims 1 to 4, wherein the first layer is loaded with 1.0 to 300 g / ft 3 The palladium loaded on the alumina component and the oxygen storage component; and the second layer loading 1.0 to 100g / ft 3 Rhodium and 1.0 to 300 g / ft 3 The rhodium and platinum are each supported on the oxygen storage component and / or the zirconium oxide component.
15. The layered catalytic article according to any one of claims 1 to 4, wherein the first layer comprises palladium supported on the oxygen storage component and the alumina component; and the second layer comprises rhodium and platinum each supported on the oxygen storage component and palladium supported on the alumina component.
16. The layered catalytic article according to any one of claims 1 to 4, wherein the first layer comprises palladium supported on the oxygen storage component and the alumina component; and the second layer comprises rhodium supported on the oxygen storage component and platinum supported on the zirconium oxide component.
17. The layered catalytic article according to any one of claims 1 to 4, wherein the substrate is a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymer foam substrate or a woven fiber substrate.
18. The layered catalytic article according to any one of claims 1 to 4, wherein the thermal fixing involves depositing platinum and / or palladium onto the support by incipient wetness impregnation, followed by thermal calcination of the resulting mixture of platinum and / or palladium and the support.
19. A method for preparing a layered catalytic article according to any one of claims 1 to 18, wherein the method comprises: preparing a first layer of slurry; depositing the first layer slurry on a substrate to obtain a first layer; preparing a second layer of slurry; and depositing the second layer slurry on the first layer to obtain a second layer, followed by calcination at a temperature in the range of 400°C to 700°C, wherein the step of preparing the first layer slurry or the second layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation and post-addition.
20. An exhaust system for an internal combustion engine, the system comprising the layered catalytic article according to any one of claims 1 to 18.
21. An exhaust system according to claim 20, wherein the system comprises a platinum group metal-based three-way conversion (TWC) catalytic product and a layered catalytic product according to any one of claims 1 to 18, wherein the platinum group metal-based three-way conversion (TWC) catalytic product is positioned downstream of an internal combustion engine, and the layered catalytic product is positioned downstream and fluidically connected to the platinum group metal-based three-way conversion (TWC) catalytic product.
22. An exhaust system according to claim 20, wherein the system comprises a platinum group metal-based three-way conversion (TWC) catalytic product and a layered catalytic product according to any one of claims 1 to 18, wherein the layered catalytic product is positioned downstream of an internal combustion engine, and the platinum group metal-based three-way conversion (TWC) catalytic product is positioned downstream and fluidically connected to the layered catalytic product.
23. A method of treating a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides, the method comprising contacting the gaseous exhaust stream with a layered catalytic article according to any one of claims 1 to 18 or an exhaust system according to any one of claims 20 to 22.
24. A method for reducing the levels of hydrocarbons, carbon monoxide and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a layered catalytic article according to any one of claims 1 to 18 or an exhaust system according to any one of claims 20 to 22 to reduce the levels of hydrocarbons, carbon monoxide and nitrogen oxides in the gaseous exhaust stream.
25. Use of a catalytic article according to any one of claims 1 to 18 for the purification of a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides.
